Implementasi Supervisi Klinis dalam Peningkatan Kompetensi Pedagogik Guru Mata Pelajaran Pendidikan Agama Islam di MAN 2 Bone - Hartati, Hartati (JURNAL AL-QAYYIMAH, 2019)
The implementation of clinical supervision is the provision of coaching by the headmaster to teachers through learning planning activities, systematic implementation of learning activities, then evaluated where the position of excess and Lack of his studies so that in the future teachers can find ways to improve his teaching performance. Not a few problematics faced by the teacher. Complex and complex issues have their own characteristics. It is necessary to understand the characteristics of clinical supervision. So important the principal conducts supervision such as clinical supervision as a monitoring to the teacher's performance automatically to obtain information about the achievement of students' learning outcomes or student learning achievements. Clinical supervision as one of the types of supervision that seeks to guide teachers on learning activities through the cycle and ongoing, and is one of the efforts to improve the performance of qualified teachers.Implementasi supervisi klinis adalah pemberian pembinaan oleh kepala sekolah kepada guru melalui kegiatan perencanaan pembelajaran, pelaksanaan kegiatan pembelajaran yang sistematis, kemudian dievaluasi di mana posisi kelebihan dan Kekurangan studinya sehingga di masa depan guru dapat menemukan cara untuk meningkatkan kemampuannya. kinerja mengajar. Tak sedikit masalah yang dihadapi guru. Masalah kompleks dan kompleks memiliki karakteristiknya sendiri. Penting untuk memahami karakteristik pengawasan klinis. Begitu pentingnya kepala sekolah melakukan pengawasan seperti pengawasan klinis sebagai pemantauan terhadap kinerja guru secara otomatis untuk mendapatkan informasi tentang pencapaian hasil belajar siswa atau prestasi belajar siswa. Pengawasan klinis sebagai salah satu jenis pengawasan yang berupaya membimbing guru pada kegiatan pembelajaran melalui siklus dan berkelanjutan, dan merupakan salah satu upaya untuk meningkatkan kinerja guru yang berkualitas.